2014
DOI: 10.1097/md.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Askin Tumor

Abstract: The aim of the study was to describe the imaging findings of Askin tumors on computed tomography (CT) and fluorine 18 fluorodeoxyglucose-positron emission tomography (FDG-PET/CT).Seventeen cases of Askin tumors confirmed by histopathology were retrospectively analyzed in terms of CT (17 cases) and FDG-PET/CT data (6 cases).Fifteen of the tumors were located in the chest wall and the other 2 were in the anterior middle mediastinum. Of the 15 chest wall cases, 13 demonstrated irregular, heterogeneous soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…evaluated 6 patients of Askin tumor with 18 F-FDG PET and observed that the lesion SUV max varied from 4.0 to 18.6. [ 8 ] However, Kara Gedik et al . reported a SUV max of 4.3 in their case report of 73-year-old male with Askin tumor.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated 6 patients of Askin tumor with 18 F-FDG PET and observed that the lesion SUV max varied from 4.0 to 18.6. [ 8 ] However, Kara Gedik et al . reported a SUV max of 4.3 in their case report of 73-year-old male with Askin tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated catecholamine levels seen in neuroblastoma differentiate it from Askin tumor [6] . In addition, neuroblastomas are known to have early enhancement, invade surrounding vasculature, and in contradistinction to the typical Askin tumors, may show coarse calcifications [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular enhancement after intravenous gadolinium may occur and indicates neoplastic hypervascularity [1] . Fluorodeoxyglucose-positron emission tomography/CT may also help provide clarification, as Askin tumors have presented as fluorodeoxyglucose-avid masses [7] . Nevertheless, no set of imaging characteristics are pathognomonic for Askin tumors.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, about 3/4 of cancer patients die of bone metastasis [2]. If the location and symptoms of the tumor are not obvious to the patient, metastatic bone tumors are easily misdiagnosed and even diagnosed and treated as primary bone tumors [3]. MAG-NETIC resonance whole-body diffusion imaging (MR whole-body diffusion imaging) makes use of the characteristic of limited movement of water molecules in tumor tissue cells so that bone metastases show high signal on DWI and are diagnosed [4].…”
Section: Introductionmentioning
confidence: 99%